A new Alpiscorpius from İstanbul Province of Turkey (Scorpiones: Euscorpiidae) - Tropea, Gioele; Yağmur, Ersen Aydın; Parmakelis, Aristeidis (Biologia Serbica, 2024)
A new scorpion species, Alpiscorpius istanbulensis sp. n., from Istanbul Province, Turkey, is described based on morphological and molecular evidence, raising the number of Euscorpiinae species to 19, including 12 related or phylogenetically close to the genus Alpiscorpius.